Ecological Aspects of Social Evolution : Birds and Mammals. - Rubenstein, Daniel I.; Wrangham, Richard W. (Princeton : Princeton University Press, 2014)
Seeking common principles of social evolution in different taxonomic groups, the contributors to this volume discuss eighteen groups of birds and mammals for which long-term field studies have been carried out. They examine how social organization is shaped by the interaction between proximate ecological pressures and culture""--The social traditions already in place and shaped by local and phylogenetic history. Originally published in 1987. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from t
Cover -- Contents
Print version record.
Cover; Contents.
eBooks on EBSCOhost
Keywords: Mammals -- Behavior; Mammals -- Ecology; Mammals -- Evolution; Birds -- Behavior; Birds -- Ecology; Birds -- Evolution; Social evolution in animals; Mammifères -- Mœurs et comportement; Mammifères -- Écologie.; Mammifères -- Évolution.; Oiseaux -- Mœurs et comportement; Oiseaux -- Évolution.; Évolution sociale chez les animaux; SCIENCE -- Environmental Science; SCIENCE -- Life Sciences -- Zoology -- General; Birds -- Behavior; Birds -- Ecology; Birds -- Evolution; Mammals -- Behavior; Mammals -- Ecology; Mammals -- Evolution; Social evolution in animals